The handbook of media and mass communication theory - Fortner, Robert S.; Fackler, Mark (Chichester, West Sussex, UK : Wiley, 2014)
This book presents a comprehensive collection of original essays that focus on all aspects of current and classic theories and practices relating to media and mass communication. It focuses on all aspects of current and classic theories and practices relating to media and mass communication. It includes essays from a variety of global contexts, from Asia and the Middle East to the Americas. It gives niche theories new life in several essays that use them to illuminate their application in specific contexts. It features coverage of a wide variety of theoretical perspectives. It pays close attention to the use of theory in understanding new communication contexts, such as social media.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed May 2, 2014).
Keywords: Mass media -- Research; Communication -- Research; Social media; PSYCHOLOGY -- Social Psychology; Communication -- Research; Mass media -- Research; Social media; Communicatie; Massamedia; Massenmedien; Massenkommunikation; Medientheorie; Electronic books; Handbooks and manuals; Handboeken (vorm); Handbooks and manuals